PELATIHAN DESAIN PEMBUATAN ID CARD UNTUK KEGIATAN EKSTRA KURIKULER PHOTOSHOP BAGI SISWA SMA TARSISIUS 2 JAKARTA - Suraidi (Jurnal Serina Abdimas, 2024)
This activity is in partnership with SMA Tarsisius 2 Jakarta which is located in Batusari, West Jakarta. Mitra has regular activities, namely extra-curricular school activities, one of which is photoshop training. The school did not have the human resources to teach this activity, and asked for help from the Untar PKM team. The solution given was to agree to become a teacher for Photoshop training activities in extra-curricular school subjects. The method used is direct practice in designing several products, such as posters, flyers, t-shirts, Tumblrs, ID cards. This training is to design an ID card that will be used for identification in photoshop extra-curricular activities in the even semester of 2023-2024. The training material starts from explaining each step to completing the design, and if there are modifications to the ID card design, it depends on the creativity of each participant and the results of the printed design. The training was attended by 18 students and the activities were carried out in a computer laboratory room, with each participant using a school computer that had Adobe Photoshop CS5 version installed. The final result of this training is that each participant's design is printed and given to the student ABSTRAK Kegiatan ini bermitra dengan SMA Tarsisius 2 Jakarta yang terletak di Batusari Jakarta Barat. Mitra mempunyai kegiatan rutin yaitu kegiatan ektra kurikuler sekolah, yang salah satunya adalah pelatihan photoshop. Pihak sekolah tidak mempunyai SDM untuk mengajar kegiatan ini, dan meminta bantuan tim PKM Untar. Solusi yang diberikan yaitu menyanggupi menjadi pengajar untuk kegiatan pelatihan photoshop pada mata pelajaran ektra kurikuler sekolah. Metode yang dilakukan yaitu praktek langsung mendesain beberapa produk, seperti poster, flyer, kaos, tumblr, ID card. Pelatihan ini untuk membuat desain sebuah ID card yang digunakan untuk tanda pengenal pada kegiatan ektra kurikuler photoshop pada semester genap tahun 2023-2024. Materi pelatihan di mulai dari penjelasan setiap langkah sampai selesai pembuatan desain, dan bila ada modifikasi desain ID card ini, tergantung dari kreativitas masing-masing peserta dan hasil desain dicetak. Pelatihan dihadiri oleh 18 orang siswa dengan ruang kegiatan dilakukan dalam ruang laboratorium komputer, dengan masing-masing peserta menggunakan komputer sekolah yang sudah di pasang software adobe photoshop versi CS5. Hasil akhir dari pelatihan ini yaitu hasil desain setiap peserta dicetak, dan diberikan kepada para siswa.